The Politics of ‘Bare Life’ in Sharon Bala’s The Boat People: A Biopolitical Perspective - Sharma, Pradip (SCHOLARS: Journal of Arts & Humanities, 2020)
Through the biopolitical study, this paper digs out the problems of five hundred survivors who enmeshed in the war torn Sri Lanka and Canadian sovereign power as projected in Sharon Bala’s The Boat People that dramatizes the problems of the immigrants. A large number of Tamil people escape from Sri Lanka to Canada because they were under extortion and duress in their homeland. Unlike their expectation to get a safe haven in Canada, they undergo Ariadne’s thread like unending trial for refugee status. Neither they enjoy rights at home nor abroad, which the novel dramatizes and subscribes Foucauldian biopolitics, which investigates into the effect of politics in human life. Largely in biopolitics, politics imbricates into life. The asylum seekers from Sri Lanka in Canada fall victim of power technology at home and abroad. They are subjugated to endure the hegemony of the regime that reduces them into ‘homo sacer’ whom injustice can be done with impunity and their life into bare life, life without political rights. Like a muselmann figure during the holocaust, they undergo the trial and are kept in between belonging and non-belonging, which is inclusive exclusion. They strand like the persona non grata whose significance as human is outnumbered.